Auricular acupuncture for spinal cord injury related neuropathic pain: a pilot controlled clinical trial. (4th July 2017) - Estores, Irene; Chen, Kevin; Jackson, Brian; Lao, Lixing; Gorman, Peter H.
Abstract : Objective : To obtain preliminary data on the effects of an auricular acupuncture protocol, Battlefield Acupuncture (BFA), on self-reported pain intensity in persons with chronic Spinal Cord Injury (SCI) and neuropathic pain. Design : Pilot randomized delayed entry single center crossover clinical trial at an outpatient rehabilitation and integrative medicine hospital center. Methods : Chronic (> one year post injury) ASIA impairment scale A through D individuals with SCI with injury level from C3 through T12 and below level neuropathic pain with at least five on the Numeric Rating Scale (NRS) were recruited. Twenty-four subjects were randomized to either an eight-week once weekly ten-needle BFA protocol (n = 13) or to a waiting list followed by the BFA protocol (n = 11). Outcome measures : The primary outcome measure was change in the pain severity NRS. Secondary outcome was the Global Impression of Change. Results : Demographically there were no significant differences between groups. Mean pain scores at baseline were higher in acupuncture than control subjects (7.75 ± 1.54 vs. 6.25 ± 1.04, P = 0.027). Although both groups reported significant reduction in pain during the trial period, the BFA group reported more pain reduction than the delayed entry group (average change in NRS at eight weeks –2.92 ± 2.11 vs. −1.13 ± 2.14, P = 0.065). There was a significant difference in groups when a group-by-time interaction in a mixed-effect repeated measures model (P = 0.014). Conclusion : This pilot study has provided proof of concept that BFA has clinically meaningful effect on the modulation of SCI neuropathic pain.